Home appliances remote control using microcontroller & power line - Tan Ai Ling (Universiti Malaysia Perlis, 2008)
Today’s technology a lot of countries are in pursuit to advance in science and technology , for example in Japan, America, China. The purpose is to designed a system, which is to make life easier for consumer. For this project the title is “Home Appliances Remote Control Using Microcontroller and Power Line” this project actually is a prototype that enable to implement an electrical device switch control, combining the wireless technology and domestic power line. However, this system also combining with using microcontroller programming as the main information source to code the data has be use and send out to power line to function the equipments. Implementation of this project not only to make consumer life easier but also to reuse the domestic power line without implementing big costs .The concept of this project actually to built a new system to control many electrical devices in house by using a single remote controller, the user has distance from the switch, it have still can be control many electrical devices in home.